Porous ceramic-alkali carbonate monolithic adsorbent, preparation method and application

By loading alkali metal carbonate on porous ceramic carrier and modifying urea, the problems of low loading rate and small adsorption of the integral adsorbent are solved, and efficient carbon dioxide adsorption and stability are achieved, and carbon dioxide capture technology is used to capture the technology. Provides low-cost, large-scale solutions.

CN119215846APending Publication Date: 2024-12-31CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411589849.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing monolithic adsorbents have problems such as low loading rate of alkali metal carbonate, small adsorption amount of CO2 and poor cycle stability. The preparation process is complex and the cost is high, making it difficult to meet the needs of large-scale industrial applications.

Method used

Porous ceramics such as cordierite honeycomb ceramics, mullite honeycomb ceramics, etc. are used as carriers to load alkali metal carbonates, and urea modification treatment can improve the load rate and adsorption performance of alkali metal carbonates and increase the adsorption amount of carbon dioxide. .

Benefits of technology

Achieve high alkali metal carbonate loading rate and carbon dioxide adsorption, solve the problems of poor cycle stability, complex preparation process and high cost, and provide an integrated production of excellent performance and low-cost large-scale production for carbon dioxide capture technology. Adsorbent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215846A_ABST
    Figure CN119215846A_ABST
Patent Text Reader

Abstract

The invention relates to a porous ceramic-alkali carbonate monolithic adsorbent as well as a preparation method and application thereof. The porous ceramic-alkali carbonate monolithic adsorbent comprises porous ceramic and alkali carbonate loaded on the porous ceramic. The invention also provides a preparation method of the porous ceramic-alkali carbonate monolithic adsorbent, which mainly comprises the steps of acid leaching treatment of the porous ceramic, loading of an alkali carbonate solution, evaporation, calcination and the like to obtain the monolithic adsorbent. The invention also provides an application of the porous ceramic-alkali carbonate monolithic adsorbent in adsorption of carbon dioxide in industrial flue gas. According to the invention, the problems of low alkali carbonate loading rate, small adsorption capacity and poor stability of the existing monolithic adsorbent are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon dioxide capture, and in particular to a porous ceramic-alkali metal carbonate monolithic adsorbent, a preparation method and application thereof. Background Art

[0002] The extensive use of fossil fuels has released a large amount of carbon dioxide into the atmosphere, which has led to global climate change. In order to reduce carbon dioxide emissions caused by the use of fossil fuels, carbon dioxide capture, utilization and storage (CCUS) technology has become an important technical option. Among them, alkali metal carbonate adsorption CO2 technology such as K2CO3 and Na2CO3, as an important component of CCUS technology, has important value in regulating global warming and promoting sustainable economic development.

[0003] As a kind of efficient low-temperature adsorbent, alkali metal carbonates have significant advantages such as low volatility, stable adsorption performance and low regeneration energy consumption. However, when alkali metal carbonates are directly used, there are problems such as limited CO2 transmission and low reaction activity. In addition, when CO2 adsorption is carried out on reactors such as fixed beds or fluidized beds, the adsorbent needs to be in a granular form to facilitate gas circulation and reduce resistance losses. Therefore, alkali metal carbonates such as K2CO3 and Na2CO3 are usually loaded on spherical particle carriers of Al2O3, SiO2 and ZrO2 with stable porous structures, or alkali metal carbonates are formed into particles with carrier materials, modifiers, etc. by extrusion spheronization, graphite casting and hydrophobic interface assisted methods. Although the granular adsorbent obtained by the above method has high mechanical strength, it has problems such as complicated preparation process, large material loss and high economic cost, which is difficult to meet the needs of large-scale industrial applications.

[0004] Compared with granular adsorption materials such as spheres, the route of loading alkali metal carbonates on porous ceramic carriers to obtain monolithic adsorbents has good potential for large-scale production and application due to the advantages of the porous ceramic carriers themselves, such as mature technology, wide application, and controllable costs. However, the current work on monolithic adsorbents is still very limited, mainly for air source CO2 capture, and there are many problems in the use of raw materials, preparation process, and CO2 capture performance. There are reports in the prior art that activated carbon honeycombs are loaded with hydrated K2CO3 to capture CO2 in ambient air, but its K2CO3 loading rate is very low, only 5.58wt%, and the maximum capture capacity is also very limited, with the CO2 adsorption amount reaching only 0.249mmol / g. In addition, CN111495410A discloses a honeycomb ceramic-porous carbon integral adsorbent and its preparation method and application. The adsorbent is composed of a honeycomb ceramic-porous carbon integral composite material and an organic amine, and the carbon dioxide adsorption capacity is only 0.515 mmol / g (Example 5 with the highest CO2 adsorption performance is selected, and the calculation method is the carbon dioxide adsorption capacity divided by the sum of the masses of the porous carbon, the organic amine and the honeycomb ceramic carrier). In addition, the preparation process of the honeycomb ceramic-porous carbon integral composite material is complicated, and the organic amine has the problems of high cost and poor stability, which makes its application potential relatively limited. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a porous ceramic-alkali metal carbonate monolithic adsorbent, a preparation method and an application, so as to solve the problems of low alkali metal carbonate loading rate, small CO2 adsorption amount and poor cycle stability of existing monolithic adsorbents.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A porous ceramic-alkali metal carbonate monolithic adsorbent, comprising a porous ceramic and an alkali metal carbonate supported on the porous ceramic; The porous ceramic is selected from at least one of cordierite honeycomb ceramics, mullite honeycomb ceramics, alumina foam ceramics and other porous ceramics.

[0007] According to the above technical means, by using at least one of the porous ceramics such as cordierite honeycomb ceramics, mullite honeycomb ceramics, alumina foam ceramics as a carrier and loading alkali metal carbonate on the porous ceramics, the alkali metal carbonate loading rate and stability are effectively improved, thereby increasing the adsorption amount of carbon dioxide.

[0008] Preferably, the pores of the porous ceramic can be selected from circular holes with a pore size of 1 to 2 mm.

[0009] Preferably, the alkali metal carbonate is selected from one or both of sodium carbonate and potassium carbonate.

[0010] Preferably, the loading rate of the alkali metal carbonate is at least 20 wt %.

[0011] Preferably, the porous ceramic-alkali metal carbonate monolithic adsorbent is further modified with urea.

[0012] The porous ceramic-alkali metal carbonate monolithic adsorbent was modified by urea, and the adsorption performance of the adsorbent was further improved.

[0013] The present invention also provides a method for preparing a porous ceramic-alkali metal carbonate monolithic adsorbent, comprising the following steps: S1, soaking the porous ceramic in an acid solution, drying, and calcining to obtain a porous ceramic intermediate; S2. The porous ceramic intermediate is immersed in an alkali metal carbonate solution, dried, and calcined to obtain a monolithic adsorbent.

[0014] Preferably, the S2 further includes: adding urea to the alkali metal carbonate solution to obtain a mixed solution; The porous ceramic intermediate is immersed in the mixed solution, dried and calcined to obtain a modified integral adsorbent.

[0015] The amount of urea added to the mixed solution is 1-10 wt %.

[0016] Preferably, the amount of urea added to the mixed solution is 3 wt %.

[0017] The porous ceramic-alkali metal carbonate monolithic adsorbent is modified by adding urea to the alkali metal carbonate solution, thereby further improving the adsorption capacity of carbon dioxide by the porous ceramic-alkali metal carbonate monolithic adsorbent.

[0018] Preferably, in S1, the acid solution is selected from at least one of oxalic acid solution, hydrochloric acid solution, nitric acid solution and sulfuric acid solution.

[0019] Preferably, in S1, the soaking treatment time is 2 to 8 hours.

[0020] Preferably, in S1, the soaking treatment time is 4 hours.

[0021] Preferably, the calcination temperature in S1 and S2 is 300-600°C.

[0022] Preferably, in S1, the calcination temperature is 450°C.

[0023] Preferably, both S1 and S2 are calcined in air for 2 to 6 hours.

[0024] Preferably, in S1, the calcination time is 2 hours.

[0025] Preferably, in S2, the calcination temperature is 300°C.

[0026] Preferably, in S2, the calcination time is 3 hours.

[0027] Preferably, in S2, ultrasonic assistance is used during the impregnation process.

[0028] Preferably, in S2, the loading rate of the alkali metal carbonate in the monolithic adsorbent is 20-40 wt%.

[0029] Preferably, in S2, the loading rate of alkali metal carbonate is 36 wt %.

[0030] The present invention also provides an application of a porous ceramic-alkali metal carbonate monolithic adsorbent for adsorbing carbon dioxide in industrial flue gas.

[0031] Beneficial effects of the present invention: The porous ceramic-alkali metal carbonate monolithic adsorbent of the present invention can achieve a higher alkali metal carbonate loading rate on the porous ceramic carrier, thereby improving the carbon dioxide adsorption capacity, solving the challenges of low alkali metal carbonate loading rate, small CO2 adsorption capacity and poor cycle stability of existing monolithic adsorbents, and effectively avoiding the common problems of monolithic adsorbents such as complex preparation process and high cost, and provides a monolithic adsorbent with excellent performance and low-cost large-scale production for the field of carbon dioxide capture technology, which has great promotion and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 (a) is a physical picture of porous ceramics. Figure 1 (bd) are EDS element distribution scans of porous ceramic-alkali metal carbonate monolithic adsorbent; Figure 2 This is a real-time curve diagram of CO2 concentration change during the adsorption experiment of the porous ceramic-alkali metal carbonate monolithic adsorbent; Figure 3 This is a comparison chart of CO2 adsorption and K2CO3 conversion rate of porous ceramic-alkali metal carbonate monolithic adsorbent; Figure 4 The adsorption amount change of the porous ceramic-alkali metal carbonate monolithic adsorbent prepared in Example 3 in twenty cycle experiments. DETAILED DESCRIPTION

[0033] The following will describe the embodiments of the present invention with reference to the preferred embodiments, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.

[0034] The present invention intends to disclose a porous ceramic-alkali metal carbonate monolithic adsorbent, a preparation method and an application thereof, so as to solve the problems of low alkali metal carbonate loading rate, small CO2 adsorption amount and poor cycle stability of existing monolithic adsorbents.

[0035] Among them, a porous ceramic-alkali metal carbonate monolithic adsorbent comprises a porous ceramic and an alkali metal carbonate supported on the porous ceramic; The porous ceramic is selected from at least one of cordierite honeycomb ceramics, mullite honeycomb ceramics, alumina foam ceramics and other porous ceramics.

[0036] Exemplarily, the pores of the porous ceramic may be selected from round pores and square pores, and the pore size is 1-2 mm.

[0037] In some embodiments, the alkali metal carbonate is selected from one or both of sodium carbonate and potassium carbonate.

[0038] In some embodiments, the loading of the alkali metal carbonate is at least 20 wt %.

[0039] In some embodiments, the porous ceramic-alkali metal carbonate monolithic adsorbent is further modified with urea.

[0040] In some embodiments, a method for preparing a porous ceramic-alkali metal carbonate monolithic adsorbent is also provided, comprising the following steps: S1, soaking the porous ceramic in an acid solution, drying, and calcining to obtain a porous ceramic intermediate; S2. The porous ceramic intermediate is immersed in an alkali metal carbonate solution, dried, and calcined to obtain a monolithic adsorbent.

[0041] In some embodiments, in order to further improve the adsorption performance of the porous ceramic-alkali metal carbonate monolithic adsorbent and further improve the adsorption amount of carbon dioxide, S2 further includes: adding urea to the alkali metal carbonate solution to obtain a mixed solution; The porous ceramic intermediate is immersed in the mixed solution, dried and calcined to obtain a modified integral adsorbent.

[0042] The amount of urea added to the mixed solution is 1-10wt%.

[0043] In some embodiments, in S1, the acid solution is selected from at least one of oxalic acid solution, hydrochloric acid solution, nitric acid solution and sulfuric acid solution.

[0044] In some embodiments, in S1, the soaking treatment time is 2 to 8 hours.

[0045] Exemplarily, in S1, the soaking treatment time is 4 hours.

[0046] In some embodiments, the calcination temperature in S1 and S2 is 300-600°C.

[0047] In some embodiments, both S1 and S2 are calcined in air, and the calcination time is 2 to 6 hours.

[0048] Exemplarily, in S1, the calcination temperature is 450°C.

[0049] Exemplarily, in S1, the calcination time is 2 h.

[0050] Exemplarily, in S2, the calcination temperature is 300°C.

[0051] Exemplarily, in S2, the calcination time is 3 h.

[0052] Exemplarily, in S2, ultrasound assistance is combined in the impregnation process.

[0053] In some embodiments, in S2, the loading rate of the alkali metal carbonate is 20-40 wt %.

[0054] Exemplarily, in S2, the loading rate of alkali metal carbonate is 36 wt %.

[0055] In some embodiments, a porous ceramic-alkali metal carbonate monolithic adsorbent is provided for use in adsorbing carbon dioxide in industrial flue gas.

[0056] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the preparation method of the porous ceramic-alkali metal carbonate monolithic adsorbent of the present invention will be further described in detail below in combination with specific embodiments and drawings. Obviously, the specific embodiments described are only part of the embodiments in the present application, not all of them. The following description of at least one exemplary embodiment is actually merely illustrative and is by no means a limitation on the present application and its applications. Based on the specific embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present application.

[0057] If no specific techniques or conditions are specified in the specific embodiments, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0058] like Figure 1 As shown in (a), a method for preparing a porous ceramic-alkali metal carbonate monolithic adsorbent comprises the following steps: S1. Soak the cordierite honeycomb ceramic in a 20wt% oxalic acid solution for 4 hours, take it out and wash it with deionized water until it is neutral, dry it and place it in a muffle furnace and calcine it in air at a temperature of 450°C for 2 hours to obtain a porous ceramic intermediate; the mass of the porous ceramic intermediate is 2.1984g; S2. Dissolve 4 g of K2CO3 in 16 mL of deionized water to prepare a K2CO3 solution with a mass percentage of 20 wt%; place the porous ceramic intermediate obtained in S1 in the K2CO3 solution for ultrasonic-assisted impregnation for 1 hour, then take out the impregnated cordierite honeycomb ceramic, put it into a drying oven at a temperature of 120°C for drying, then put the dried cordierite honeycomb ceramic into a muffle furnace and calcine it in air at a temperature of 300°C for 3 hours, take it out after calcination is completed and cooled to room temperature, weigh the mass of the calcined cordierite honeycomb ceramic to be 2.8043 g, and obtain a porous ceramic-alkali metal carbonate monolithic adsorbent with a K2CO3 loading rate of 22 wt%, recorded as K22.

[0059] like Figure 1 As shown in (a), a method for preparing a porous ceramic-alkali metal carbonate monolithic adsorbent comprises the following steps: S1. Soak the cordierite honeycomb ceramic in a 20wt% oxalic acid solution for 4 hours, take it out and wash it with deionized water until it is neutral, dry it and place it in a muffle furnace and calcine it in air at a temperature of 450°C for 2 hours to obtain a porous ceramic intermediate; the mass of the porous ceramic intermediate is 2.2512g; S2. Dissolve 8 g of K2CO3 in 12 mL of deionized water to prepare a K2CO3 solution with a mass percentage of 40 wt%; place the porous ceramic intermediate obtained in S1 in the K2CO3 solution for ultrasonic-assisted impregnation for 1 hour, then take out the impregnated cordierite honeycomb ceramic, put it into a drying oven at a temperature of 120°C for drying, then put the dried cordierite honeycomb ceramic into a muffle furnace and calcine it in air at a temperature of 300°C for 3 hours, take it out after calcination is completed and cooled to room temperature, weigh the mass of the calcined cordierite honeycomb ceramic to be 3.5485 g, and obtain a porous ceramic-alkali metal carbonate monolithic adsorbent with a K2CO3 loading rate of 36 wt%, recorded as K36.

[0060] like Figure 1 As shown in (a), a method for preparing a porous ceramic-alkali metal carbonate monolithic adsorbent comprises the following steps: S1. Soak the cordierite honeycomb ceramic in a 20wt% oxalic acid solution for 4 hours, wash it with deionized water until it is neutral, dry it, place it in a muffle furnace and calcine it in air at 450°C for 2 hours to obtain a porous ceramic intermediate; the mass of the porous ceramic intermediate is 2.2836g; S2. Dissolve 8 g of K2CO3 and 0.6 g of urea in 11.4 mL of deionized water to prepare a mixed solution with a mass fraction of K2CO3 of 40 wt% and a mass fraction of urea of ​​3 wt%; place the porous ceramic intermediate obtained in S1 in the mixed solution for ultrasonic-assisted impregnation for 1 hour, then take out the impregnated cordierite honeycomb ceramic, put it into a drying oven at a temperature of 120°C for drying, and then put the dried cordierite honeycomb ceramic into a muffle furnace and calcine it in air at a temperature of 300°C for 3 hours. During the calcination process, urea is completely thermally decomposed. After the calcination is completed and cooled to room temperature, take it out and weigh the mass of the calcined cordierite honeycomb ceramic to be 3.5867 g, thus obtaining a modified porous ceramic-alkali metal carbonate monolithic adsorbent with a K2CO3 loading rate of 36 wt%, recorded as K36-U3.

[0061] Detection and analysis 1) Scanning electron microscopy analysis The porous ceramic-alkali metal carbonate monolithic adsorbents prepared in Examples 1 to 3 were subjected to EDS element distribution analysis. The results are as follows: Figure 1 As shown in (b~d).

[0062] Figure 1 (b) is an element distribution scan of the porous ceramic-alkali metal carbonate monolithic adsorbent K22 prepared in Example 1. It can be observed from the figure that K2CO3 is successfully and evenly loaded on the inner surface of the pores, but the loading rate is low. Figure 1 (c) Element scanning distribution diagram of the porous ceramic-alkali metal carbonate monolithic adsorbent K36 prepared in Example 2. It can be observed from the figure that although K2CO3 is successfully loaded on the inner surface of the pores, as the loading rate increases, K2CO3 shows uneven distribution. Figure 1 (d) Element scanning distribution diagram of the porous ceramic-alkali metal carbonate monolithic adsorbent K36-U3 prepared in Example 3. It can be observed from the figure that K2CO3 is successfully and evenly loaded on the inner surface of the pores, and the loading rate is high.

[0063] 2) Performance test of porous ceramic-alkali metal carbonate monolithic adsorbent The specific operation steps are: the porous ceramic-alkali metal carbonate monolithic adsorbent prepared in Example 1 to Example 3 is respectively subjected to fixed bed test, with a total flow rate of 300mL / min, of which the flow rate of CO2 is 30mL / min; the flow rate of water vapor is 60mL / min; the flow rate of N2 is 210mL / min; and adsorption is carried out at a temperature of 60°C for 50min. Then the flow rate of N2 is adjusted to 300mL / min, the flow rate of CO2 is closed, the heating rate is 10°C / min, and the temperature is raised to 180°C for desorption for 40 minutes. The performance of the adsorbent is expressed as the CO2 adsorption amount per unit mass of the adsorbent. The specific calculation is the CO2 adsorption amount divided by the mass of the monolithic adsorbent (the sum of the mass of potassium carbonate and the porous ceramic). The result is as follows: Figures 2 to 4 shown.

[0064] Figure 2 The graph is a real-time variation curve of CO2 concentration during the adsorption experiment of the porous ceramic-alkali metal carbonate monolithic adsorbent prepared in Examples 1 to 3.

[0065] from Figure 2 It can be seen from the analysis that the area difference between the CO2 concentration change of the porous ceramic-alkali carbonate monolithic adsorbent prepared in Examples 1 to 3 and the blank experiment of the porous ceramic carrier without alkali carbonate reflects the size of the CO2 adsorption capacity. The area difference between Example 1 and the blank experiment is the smallest, and the adsorption saturation is reached in about 20 minutes; the area difference between Example 2 and the blank experiment is the second largest, and the adsorption saturation is reached in about 25 minutes; the area difference between Example 3 and the blank experiment is the largest, and the adsorption saturation is reached in about 45 minutes.

[0066] Figure 3 This is a comparison chart of the CO2 adsorption capacity and K2CO3 conversion rate of the porous ceramic-alkali metal carbonate monolithic adsorbent prepared in Examples 1 to 3.

[0067] from Figure 3From the analysis, it can be seen that the CO2 adsorption capacity of the porous ceramic-alkali metal carbonate integral adsorbent prepared in Example 1 is 1.56 mmol / g, and the K2CO3 conversion rate is 97.82%; the CO2 adsorption capacity of the porous ceramic-alkali metal carbonate integral adsorbent prepared in Example 2 is 2.05 mmol / g, and the K2CO3 conversion rate is 78.92%, indicating that with the increase of the loading amount, the CO2 adsorption capacity increases, but the K2CO3 conversion rate decreases. The reason for this situation is that the increase in loading amount leads to K2CO3 particle agglomeration and pore clogging, making K2CO3 unevenly distributed, which is not conducive to CO2 adsorption. The CO2 adsorption capacity of the porous ceramic-alkali metal carbonate monolithic adsorbent prepared in Example 3 is 2.48 mmol / g, and the K2CO3 conversion rate is 97.12%, indicating that the addition of urea can significantly improve the CO2 adsorption capacity and K2CO3 conversion rate. The reason for this change is that the urea is thermally decomposed and released during the calcination process, resulting in increased porosity and a more uniform distribution of K2CO3, which is more conducive to CO2 adsorption.

[0068] Figure 4 The adsorption amount change of the porous ceramic-alkali metal carbonate monolithic adsorbent prepared in Example 3 in twenty cycle experiments.

[0069] from Figure 4 It can be seen from the analysis that the adsorption amount of the porous ceramic-alkali metal carbonate monolithic adsorbent prepared in Example 3 first increased, then decreased and finally stabilized. The adsorption amount in the second cycle was the highest, reaching 2.51 mmol / g, and it began to stabilize from the sixth cycle until the twentieth cycle, and the adsorption amount was maintained at about 2.05 mmol / g, showing good cycle stability.

[0070] In summary, the porous ceramic-alkali metal carbonate monolithic adsorbent of the present invention effectively improves the loading rate and stability of alkali metal carbonate on the porous ceramic carrier, thereby improving the carbon dioxide adsorption capacity, solving the challenges of low alkali metal carbonate loading rate, small CO2 adsorption capacity and poor cycle stability of existing monolithic adsorbents, and effectively avoiding the problems of complex preparation process and high cost of monolithic adsorbents. It provides a monolithic adsorbent with excellent performance and low-cost large-scale production for the field of carbon dioxide capture technology, which has great promotion and application value.

[0071] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present invention is within the protection scope of the present invention.

Claims

1. A porous ceramic-alkali metal carbonate monolithic adsorbent, characterized in that: It includes a porous ceramic and an alkali metal carbonate supported on the porous ceramic; The porous ceramic is selected from at least one of cordierite honeycomb ceramics, mullite honeycomb ceramics, alumina foam ceramics and other porous ceramics.

2. The porous ceramic-alkali metal carbonate monolithic adsorbent according to claim 1, characterized in that: The alkali metal carbonate is selected from one or both of sodium carbonate and potassium carbonate.

3. The porous ceramic-alkali metal carbonate monolithic adsorbent according to claim 1, characterized in that: The loading rate of the alkali metal carbonate is at least 20 wt %.

4. The porous ceramic-alkali metal carbonate monolithic adsorbent according to claim 1, characterized in that: The porous ceramic-alkali metal carbonate monolithic adsorbent is also modified with urea.

5. A method for preparing the porous ceramic-alkali metal carbonate monolithic adsorbent according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, soaking the porous ceramic in an acid solution, drying, and calcining to obtain a porous ceramic intermediate; S2. The porous ceramic intermediate is immersed in an alkali metal carbonate solution, dried, and calcined to obtain a monolithic adsorbent.

6. The preparation method according to claim 5, characterized in that: Said S2 further includes: adding urea to the alkali metal carbonate solution to obtain a mixed solution; The porous ceramic intermediate is immersed in the mixed solution, dried, and calcined to obtain a modified monolithic adsorbent; The amount of urea added to the mixed solution is 1-10 wt %.

7. The preparation method according to claim 5, characterized in that: The calcination temperature in S1 and S2 is 300-600°C; and / or, said S1 and S2 are calcined in air for 2 to 6 hours; and / or, in said S1, the acid solution is selected from at least one of oxalic acid solution, hydrochloric acid solution, nitric acid solution and sulfuric acid solution; And / or, in S1, the soaking treatment time is 2 to 8 hours.

8. The preparation method according to claim 5, characterized in that: In S2, ultrasound assistance is combined during the impregnation process.

9. The preparation method according to claim 5, characterized in that: In the S2, the loading rate of the alkali metal carbonate in the monolithic adsorbent is 20-40 wt%.

10. An application of a porous ceramic-alkali metal carbonate monolithic adsorbent, characterized in that: The porous ceramic-alkali metal carbonate monolithic adsorbent is used for adsorbing carbon dioxide in industrial flue gas.